1996
DOI: 10.3950/jibiinkoka.99.1648
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Of“anosmic Zones”associated With Nasal Allergy

Abstract: Twenty-seven nasal allergy patients suffering from olfactory disturbance were evaluated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…21 Higo et al investigated smell alterations in patients with allergic rhinitis and speculated that rhinitis causes alterations in the olfactory mucosa, resulting in olfactory transduction impairment. 22 In the present study, smell alterations in group I were found in 33.3% of individuals (13 patients), and in group II, 11.1% (two patients). Three months postoperatively, only two patients did not achieve overall symptom improvement, with no difference between the two groups.…”
Section: Discussionsupporting
confidence: 50%
“…21 Higo et al investigated smell alterations in patients with allergic rhinitis and speculated that rhinitis causes alterations in the olfactory mucosa, resulting in olfactory transduction impairment. 22 In the present study, smell alterations in group I were found in 33.3% of individuals (13 patients), and in group II, 11.1% (two patients). Three months postoperatively, only two patients did not achieve overall symptom improvement, with no difference between the two groups.…”
Section: Discussionsupporting
confidence: 50%
“…Another study maintains that decongestion of AR patients' nasal mucosa with epinephrine drops did not normalize the olfactory function 31. These studies suggest a potential role for inflammatory changes in nasal mucosa 32. Patients with AR showed a close correlation between the loss of smell and inflammatory markers such as the eosinophilic cationic protein (ECP)13 and the blood eosinophil concentration 9.…”
Section: Discussionmentioning
confidence: 85%
“…It has previously been hypothesized (14) that nVMR patients, because of their intolerance to odors and irritants, might be distinguished from patients having other forms of chronic rhinitis, due to an abnormality in their olfactory transduction pathway. Paradoxically, the limited number of studies investigating odorant discrimination found a greater magnitude of olfactory loss in nVMR patients in response to common odorants, such as formalin, camphor, asafetida (India saffron spice), and oil of peppermint-as compared with allergic rhinitis patients or control subjects without rhinitis (15).…”
Section: Introductionmentioning
confidence: 99%